2020
DOI: 10.1111/jcmm.16077
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal small RNAs are promising non‐invasive diagnostic biomarkers for gastric cancer

Abstract: Gastric cancer (GC) is the fifth most common cancer worldwide and the third leading cause of death from malignant tumours. 1 In China, the number of people who were newly diagnosed with GC was approximately 679,100 and almost 498,000 people died in 2015. 2 As most newly diagnosed with GC are identified at an advanced stage, five-year survival rate of patients is low. 3 The most common-used GC tumour markers, including carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 199, CA242 and CA724, are not sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…The RNA, protein and lipid profiles of exosomes derived from different ovarian tumors are different, and the circular RNAs carried by ovarian tumor cell-derived exosomes are also different from healthy volunteers (134). In addition, serum exosomal piwi-interacting RNAs are considered to be a promising biomarker for patients with gastric cancer (202). Researchers have found that the detection level of CA125 in exosomes is higher compared with that in serum, which significantly improves the sensitivity of ovarian cancer diagnosis (203).…”
Section: Discussionmentioning
confidence: 99%
“…The RNA, protein and lipid profiles of exosomes derived from different ovarian tumors are different, and the circular RNAs carried by ovarian tumor cell-derived exosomes are also different from healthy volunteers (134). In addition, serum exosomal piwi-interacting RNAs are considered to be a promising biomarker for patients with gastric cancer (202). Researchers have found that the detection level of CA125 in exosomes is higher compared with that in serum, which significantly improves the sensitivity of ovarian cancer diagnosis (203).…”
Section: Discussionmentioning
confidence: 99%
“…MiRs, which play roles in multiple biological processes such as exocytosis, hematopoesis and angiogenesis, participate in exosome mediated cellular communication [ 16 ]. Other exosomal RNA species include ribosomal RNA (rRNA), long non-coding RNA (lncRNA), transfer RNA (tRNA), small nuclear RNA (snRNA), small nucleolar RNA and p-element-induced wimpy testis (piwi)-interacting RNA, all of which impact biological processes, particularly influencing tumor development [ 16 , 35 ]. Studies have thus explored their potential for use as non-invasive disease diagnostic and prognostic tool.…”
Section: Biological Composition Of Exosomesmentioning
confidence: 99%
“…Martinez et al analyzed 6,260 human piRNA transcriptomes derived from non-malignant and tumor tissues of 11 organs, and discovered 273 and 522 piRNAs with expression in somatic nonmalignant tissues and corresponding tumor tissues, respectively, which were able to not only distinguish tissue-of-origin, but also distinguish tumors from non-malignant tissues in a cancer-type specific manner (15). A recent study identified the increased levels of circulating miR-1307-3p, piR-019308, piR-004918 and piR-018569 in the serum exosomes of gastric cancer patients (16). Moreover, higher levels of piR-004918 and piR-019308 were found in the gastric cancer patients with metastasis than non-metastatic patients, indicating that circulating piRNAs in serum are promising non-invasive diagnostic biomarkers for gastric cancer patients and potential markers for monitoring metastasis (16).…”
Section: Aberrant Expression Of Pirnas and Piwi Members In Cancermentioning
confidence: 99%
“…A recent study identified the increased levels of circulating miR-1307-3p, piR-019308, piR-004918 and piR-018569 in the serum exosomes of gastric cancer patients (16). Moreover, higher levels of piR-004918 and piR-019308 were found in the gastric cancer patients with metastasis than non-metastatic patients, indicating that circulating piRNAs in serum are promising non-invasive diagnostic biomarkers for gastric cancer patients and potential markers for monitoring metastasis (16). Wang et al screened piRNAs in the serum from 7 patients with colorectal cancer and 7 normal controls using small RNA sequencing, followed by QRT-PCR validation of the differentially expressed piRNAs in a training cohort of 140 patients with colorectal cancer (17).…”
Section: Aberrant Expression Of Pirnas and Piwi Members In Cancermentioning
confidence: 99%
See 1 more Smart Citation